PENGARUH PROMOSI PENJUALAN DAN SIFAT MATERIALISME TERHADAP PERILAKU IMPULSE BUYING SECARA ONLINE PADA SITUS OLX DI KOTA SAMARINDA - Safwo Alif Saputra; Rahmawati Rahmawati; Robiansyah Robiansyah (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
SAFWO ALIF SAPUTRA, 2017. the influence of sales promotion and the characteristic of materialism against the behavior of impulse buying via online on OLX site in Samarinda. Under the gudance by Mrs. Rahmawati. and Mrs Sri Wahyuni.The study aims to determine the influence of sales promotion ),  and the characteristic of materialism (),  against the behavior of impulse buying via online on OLX site in Samarinda. This research was conducted by using multiple linier regression method for collecting its data.            The result of this study indicate that the factors sales promotion and the characteristic of materialism channels simultaneously or jontly have a significant on influence the behavior of impulse buying via online on OLX site in Samarinda and between the independent variabels studied, indicating that variable materialism have a dominant influence on the behavior of impulse buying via online on OLX site in Samarinda.